2016
DOI: 10.2495/sdp-v11-n2-192-202
|View full text |Cite
|
Sign up to set email alerts
|

A water-soluble polycarbobetaine for sustainable copper recovery

Abstract: This study targets betaine-type polymers (polycarbobetaines -PCBets) as complexing agent of metal ions. As PCBets are pH-sensitive, the adsorption isotherms of copper onto PCBet were monitored at various pH (from 3 to 6) by electrochemical measurements. The best fit to the Langmuir model translates the predominantly homogeneous distribution of the chelating groups on the polymer chains because the Langmuir equation assumes that the adsorbent surface is energetically homogeneous. The results obtained for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…7 for both PCBets which differs from previous results obtained for PCEAC [5]. The methodology used in this previous article [5] was considering other metal ion adsorption favouring copper desorption. Here as exposed in Fig.…”
Section: Pcbets Experiments With Spiked Catholytesmentioning
confidence: 61%
See 4 more Smart Citations
“…7 for both PCBets which differs from previous results obtained for PCEAC [5]. The methodology used in this previous article [5] was considering other metal ion adsorption favouring copper desorption. Here as exposed in Fig.…”
Section: Pcbets Experiments With Spiked Catholytesmentioning
confidence: 61%
“…In the case of PCEAC, some copper desorption occurs (-25%) with the increase of spiking copper concentration from 77-319 mg/L. Considering our previous results [5] showing that no copper desorption takes place in the presence of Ca or Zn (whatever is the ratio between 0.5-10), it is suggested that some copper is desorbed in favour of Al adsorption. No such desorption was observed in the case of PCEAMC suggesting that the chemical structure of PCBets can lead to different properties.…”
Section: Pcbets Experiments With Spiked Catholytesmentioning
confidence: 68%
See 3 more Smart Citations